THE IMPACT OF CHILD MARRIAGE ON THE MENTAL HEALTH AND WELL-BEING OF GIRLS LIVING IN RURAL COMMUNITIES OF THE REPUBLIC OF SOUTH AFRICA - Decent Munzhelele; Mukhethwa Jane Maladza; Vhahangwele Muvhango (CV. RADJA PUBLIKA, 2025)
This study investigates the impact of child marriage on the mental health and well-being of girls living in rural communities of the Republic of South Africa. The research adopted a qualitative approach with an exploratory research design, utilizing a comprehensive desktop study to gather relevant data from existing literature, reports, and secondary sources. The study aims to examine how early marriage affects the psychological, emotional, and social aspects of young girls’ lives, focusing on the mental health challenges they face, such as depression, anxiety, trauma, and loss of autonomy. Through thematic data analysis, the study identifies key themes, including the disruption of education, social isolation, stigmatization, physical health risks, and the negative impact of cultural and societal norms surrounding marriage. The findings highlight the multifaceted nature of child marriage, revealing how it exacerbates mental health issues and limits opportunities for personal growth, social integration, and empowerment. Additionally, the study emphasizes the lack of access to mental health support services in rural communities, making it harder for these girls to overcome the psychological effects of early marriage. By shedding light on these issues, the study calls for a greater focus on policy interventions, community awareness, and mental health services to address the challenges faced by married girls in rural South Africa.